Infection of Immunodeficient Horses with Sarcocystis neurona Does Not Result in Neurologic Disease - Sellon, Debra C. (American Society for Microbiology, 2004)
Equine protozoal myeloencephalitis is a progressive neurologic disease of horses most commonly caused by infection with the apicomplexan parasite Sarcocystis neurona. Factors affecting neuroinvasion and neurovirulence have not been determined. We investigated the pathogenesis of infection with S. neurona in horses with severe combined immune deficiency (SCID). Two immunocompetent (IC) Arabian horses and two Arabian horses with SCID were infected orally with 5 × 10(5) sporocysts of S. neurona. Four IC horses and one SCID horse were infected intravenously (i.v.) with 5 × 10(8) merozoites of the WSU-1 isolate of S. neurona. Despite prolonged parasitemia and persistent infection of visceral tissues (skeletal muscle, cardiac muscle, lung, liver, and spleen) as demonstrated by PCR and culture, SCID horses did not develop neurologic signs after oral or i.v. infection. S. neurona was undetectable in the neuronal tissues of SCID horses by either PCR, immunohistochemistry, or culture. In contrast, although parasitemia was undetectable in orally infected IC horses and of only short duration in i.v. infected IC horses, four of six IC horses developed neurologic signs. S. neurona was detectable by PCR and/or culture of neural tissue but not visceral tissue of IC horses with neurologic disease. Infected SCID horses are unable to clear S. neurona from visceral tissues, but the infection does not result in neurologic signs; in contrast, IC horses rapidly control parasitemia and infection of visceral tissues but frequently experience neuroinvasion and exhibit clinical signs of neurologic disease.